Living Oprah: My One-Year Experiment to Walk the Walk of the Queen of Talk - Okrant, Robyn; OverDrive, Inc. (New York : Center Street, 2010)
A fascinating, funny and thought-provoking account of one woman's quest to live her 'best life' according to Oprah's advice for a year. My One-Year Experiment to Walk the Walk of the Queen of talk 'Shhh ... listen carefully. If you're very quiet, you can hear the echoes of screaming triggered by the surprise announcement that today's audience is being treated to Oprah's "Favorite things" for summer ... I shudder to think what I might end up adding to my to-do list by the end of the hour.' On January 1, 2008, Robyn Okrant kicked off a year- long experiment to find out what would happen if an average 35-year-old woman put her life in the hands of television's most influential personality, Oprah Winfrey. Using the Oprah Winfrey Show, O, the Oprah Magazine and Oprah.com as a roadmap for her journey, her rule was whatever Oprah says, she does. From her wardrobe to her marriage, diet, spiritual life, finances, home and beyond, the author redesigned her entire life according to Winfrey's 'best life' advice. Why Oprah? Hers is the quintessential rags-to-riches story, and her 'Live Your Best Life' theme inspires millions to strive for happier, more productive lives. And of all the cultural influences on women, Oprah is one of the most prevalent and powerful. Funny, fascinating and thought-provoking, LIVING OPRAH chronicles the author's odyssey as she moves in and out of her comfort zone - sometimes exhilarated, sometimes exhausted and often bemused - while exploring just how much influence any one person, even Oprah, should have on others.
January : what have I gotten myself into? -- February : an enterprising month -- March : if the leopard- print shoe fits... -- April : clarity, enlightenment, and highlighters...Oh my! -- May : I'd kill for a burger and a latte right about now -- June : living with less while dreaming of more -- July : name that blogger -- August : America gets a report card -- September : shaky ground -- October : isn't it ironic? -- November : guess who's coming to dinner? -- December : light at the end of the tunnel -- January 2009 : basking in the afterLO.
Imprint: HarperCollins.
Requires Adobe Digital Editions (file size: 7973 KB).
Keywords: Okrant, Robyn; Winfrey, Oprah -- Influence; Okrant, Robyn; Winfrey, Oprah; Miscellaneous items; Electronic books; Women -- United States -- Biography; Women -- United States -- Conduct of life; Popular culture -- United States; Influence (Literary, artistic, etc.); Popular culture; Women; Women -- Conduct of life; United States; Australian; Electronic books; Electronic books